Variable High-Pressure-Processing Sensitivities for Genogroup II Human Noroviruses - Lou, Fangfei (Appl Environ Microbiol, 2016)
Human norovirus (HuNoV) is a leading cause of foodborne diseases worldwide. High-pressure processing (HPP) is one of the most promising nonthermal technologies for the decontamination of viral pathogens in foods. However, the survival of HuNoVs after HPP is poorly understood because these viruses cannot be propagated in vitro. In this study, we estimated the survival of different HuNoV strains within genogroup II (GII) after HPP treatment using viral receptor-binding ability as an indicator. Four HuNoV strains (one GII genotype 1 [GII.1] strain, two GII.4 strains, and one GII.6 strain) were treated at high pressures ranging from 200 to 600 MPa. After treatment, the intact viral particles were captured by porcine gastric mucin-conjugated magnetic beads (PGM-MBs) that contained histo-blood group antigens, the functional receptors for HuNoVs. The genomic RNA copies of the captured HuNoVs were quantified by real-time reverse transcriptase PCR (RT-PCR). Two GII.4 HuNoVs had similar sensitivities to HPP. The resistance of HuNoV strains against HPP ranked as follows: GII.1 > GII.6 > GII.4, with GII.4 being the most sensitive. Evaluation of temperature and matrix effects on HPP-mediated inactivation of HuNoV GII.4, GII.1, and GII.6 strains showed that HuNoV was more easily inactivated at lower temperatures and at a neutral pH. In addition, phosphate-buffered saline (PBS) and minimal essential medium (MEM) can provide protective effects against HuNoV inactivation compared to H(2)O. Collectively, this study demonstrated that (i) different HuNoV strains within GII exhibited different sensitivities to high pressure, and (ii) HPP is capable of inactivating HuNoV GII strains by optimizing pressure parameters. IMPORTANCE Human norovirus (HuNoV) is a leading cause of foodborne disease worldwide. Noroviruses are highly diverse, both antigenically and genetically. Genogroup II (GII) contains the majority of HuNoVs, with GII genotype 4 (GII.4) being the most prevalent. Recently, GII.1 and GII.6 have emerged and caused many outbreaks worldwide. However, the survival of these GII HuNoVs is poorly understood because they are uncultivable in vitro. Using a novel receptor-binding assay conjugated with real-time RT-PCR, we found that GII HuNoVs had variable susceptibilities to high-pressure processing (HPP), which is one of the most promising food-processing technologies. The resistance of HuNoV strains to HPP ranked as follows: GII.1 > GII.6 > GII.4. This study highlights the ability of HPP to inactivate HuNoV and the need to optimize processing conditions based on HuNoV strain variability and sample matrix.